Raddeanin A suppresses lung cancer cell proliferation via induction of apoptosis and increased production of ROS - Jin, Weiguo; Lu, Shichun; Wang, Xiaolin; Shu, Yusheng; Shi, Hongcan (Cellular and Molecular Biology, 2020)
At present, in vitro cell experiments have confirmed that RaddeaninA can effectively inhibit the proliferation of some tumor cells, but the effect of RaddeaninA on lung cancer cells has not been observed. Therefore, this study explored its effect on lung cancer cells and its mechanism of action. Human lung cancer cell lines were treated with serum-free medium and varied concentrations of Raddeanin A. Cell proliferation and apoptosis were determined using MTT, and flow cytometric assays, respectively. The intracellular level of ROS was determined using DCFH-DA assay. Protein and mRNA expressions of bax, bcl-2 and cyt c were measured using Western blotting and qRT-PCR. RaddeaninA treatment can promote PC-9 cell apoptosis in a time and dose-dependent manner (p<0.05). Treatment of PC-9 cells with Raddeanin significantly and dose-dependently increased the activities of caspase-9 and caspase-3 (p<0.05), and led to significant and dose-dependent increases in ROS levels (p<0.05). Treatment of PC-9 cells with Raddeanin A led to significant and dose-dependent decreases in mitochondrial membrane potential (p<0.05). It significantly and dose-dependently upregulated bax mRNA and protein expressions, but down-regulated bcl-2 mRNA and protein expressions significantly and dose-dependently (p<0.05). On the other hand, Raddeanin significantly and dose-dependently down-regulated cytoplasmic bax protein expression, while upregulating cyt c expression (p<0.05). Similarly, bax protein expression was significantly and dose-dependently upregulated in mitochondria, but the corresponding cyt c expression was significantly and dose-dependently down-regulated (p<0.05). Raddeanin A is a potential and effective lung cancer chemotherapy drug, which can induce lung cancer cell apoptosis and inhibit proliferation.